Effectiveness of E-Magazine Teaching Materials on Global Warming Materials Phase E - Putri, Mutiara Duana; Hidayati, Hidayati (Universitas Lambung Mangkurat, 2024)
The independent curriculum requires teaching materials with technological development innovations, including e-magazine teaching materials. E-magazine teaching materials are teaching materials in the form of electronic magazines that can be accessed using mobile phones. The advantage of e-magazine teaching materials is that presenting interesting material with pictures and videos can increase students' interest in physics. This study aims to determine the effectiveness of electronic magazine teaching materials on student learning outcomes in the global warming material phase E of SMAN 6 Padang. The type of research conducted is quasi-experimental. The design used in the study was Randomized Control Group Only Design. The population in the study is all phase E classes of SMAN 6 Padang in the 2023/2024 school year. In this study, 2 sample classes were used with purposive sampling techniques, namely the experimental and control classes. In the learning experiment class, the learning uses e-magazine teaching materials; the learning control class uses printed teaching materials at school. The research results showed that e-magazine teaching materials effectively improve student learning outcomes on global warming materials in the independent curriculum.